Translating in Yarns and Colours: the intersemiotic translation of José de Alencar’s Iracema by the "group Iluminuras de Literatura e Bordado" - Rocha, Hyana Jessica Silveira (TradTerm, 2023)
Created in 2014, the Iluminuras Literature and Embroidery Group is an extension project of the Federal University of Ceará (UFC), linked to the Pedagogy course and has as its main objective the encouragement of reading. Every semester, the group studies a classic of Brazilian literature, discusses about the work and how to propose a re-signification of the text in drawings, lines, and colors, projecting Brazilian literature in the visual signs of embroidery to a wider public. Such activities are categorized as a practice of intersemiotic translation, since embroidery translates the literary text into images. This work presents, through the analysis of one of the embroideries produced, the intersemiotic translation performed by the group.